Crossover promotion and prevention. (21st July 2006) - Lorenz, A.; Whitby, M.C.
Abstract : Homologous recombination is an important mechanism for the repair of double-strand breaks in DNA. One possible outcome of such repair is the reciprocal exchange or crossing over of DNA between chromosomes. Crossovers are beneficial during meiosis because, as well as generating genetic diversity, they promote proper chromosome segregation through the establishment of chiasmata. However, crossing over in vegetative cells can potentially result in loss of heterozygosity and chromosome rearrangements, which can be deleterious. Consequently, cells have evolved mechanisms to limit crossing over during vegetative growth while promoting it during meiosis. Here, we provide a brief review of how some of these mechanisms are thought to work.